Association of serum sodium concentration with coronary atherosclerosis in China： follow-up study - Jia, En-zhi; Xu, Zhen-xia; Yang, Zhi-jian; Zhu, Tie-bing; Wang, Lian-sheng; Chen, Bo; Cao, Ke-jiang; Huang, Jun; Ma, Wen-zhu; Lu, Xiang (Acta pharmacologica Sinica, 2009)
Aim： The aim of this study was to test the hypothesis that lower serum sodium may be associated with increased cardiovascular events and all-cause mortality by means of long-term follow-up of subjects with coronary atherosclerosis in a prospective, hospital-based epidemiological study in China. Methods： A prospective, hospital-based epidemiological design was used. The study population consisted of 1069 consecutive patients who were scheduled to undergo coronary angiography for suspected or known coronary atherosclerosis. The severity of coronary atherosclerosis was defined using Gensini＇s score system. Age, sex-adjusted hazard ratios （HR） and 95% confidence intervals （CI） for the quartiles of serum sodium concentration were estimated with Cox proportional hazard models, using quartile 1 as the reference. Cox proportional hazard models were also constructed to estimate the hazard ratios and 95% confidence intervals for all-cause mortality and final end-point events by serum sodium quartile and to adjust for potentially confounding variables. Multivariate models were adjusted for the following variables： age, sex, smoking status, alcohol consumption, body mass index, blood pressure, potassium, chloride, total cholesterol, triglycerides, fasting blood glucose, urea, creatinine, uric acid, and Gensini＇s score. Results： During the median 2.86 years （3011.66 person-years） of follow-up, 176 final end-point events were documented. These events included 79 deaths and 97 readmissions for coronary heart disease. There was a statistically significant inverse association of serum sodium with all-cause mortality （P〈0.001）. After full adjustment comparing the highest serum sodium quartile to the lowest, there was a non-significant inverse association with all-cause mortality, with an adjusted hazard ratio （95% CI） of 0.67 （0.25-1.80）. After adjustment for age and increasing quartiles of serum sodium concentration were sex, the hazard ratio and 95% CI for final end-point events across 1.00, 0.85 （0.59-1.22）, 0.52 （0.34-0.82）, and 0.31 （0.19-0.49）. After full adjustment comparing the highest serum sodium quartile to the lowest, there was a statistically significant inverse asso- ciation with final end-point events, with an adjusted hazard ratio （95% CI） of 0.46 （0.26-0.81）. Conclusion： The serum sodium concentration showed a statistically significant negative association with coronary events and all-cause mortality in subjects with coronary atherosclerosis; the actual mechanism underlying this association needs further study.